Idiopathic Oesophageal Dysmotility Disorder: Stridor Secondary to Megaesophagus - B. G. Natesh; N. Caton; D. Kim; A. Shetty (Case Reports in Otolaryngology, 2013)
We present an interesting case of an elderly lady who presented with stridor caused by megaesophagus secondary to an acquired idiopathic dysmotility disorder. We discuss the aetiology and management of megaesophagus secondary to this condition and how it differs from megaesophagus secondary to achalasia.